Key techniques in extralevator abdominoperineal excision and pelvic floor repair for low rectal cancer - Jiang Songsong; Chen Gang (结直肠肛门外科)
［Abstract］ Extralevator abdominoperineal excision (ELAPE) can retrieve cylindrical rectal cancer surgical specimens without a“waist”, which is beneficial to reduce the positive rate of circumferential resection margin and local recurrence rate. However, the expansion of perineal resection will lead to an increased incidence of pelvic floor and perineal complications. Therefore, pelvic floor reconstruction is crucial in preventing perineal complications after ELAPE. In this paper, based on our experiences, we introduce the key techniques in ELAPE and pelvic floor reconstruction for low rectal cancer to provide references for our peers and reduce the incidence of perineal complications after ELAPE.